Evaluation of canal transportation and centering ability of K 3 (0.02%) and K 3 (0.04%) with hand K files in primary teeth using spiral computed tomography - Haridoss Selvakumar; Vasanthakumari Anandhan; Eapen Thomas; Kavitha Swaminathan; Rajendran Vijayakumar (Wolters Kluwer Medknow Publications, 2014)
Background: One of the objectives of root canal preparation is to clean and shape the root canal system while maintaining the original configuration. Therefore, it is important to keep the instruments centered to provide a correct enlargement, without excessive weakening of the root structure. Aim: The aim of the study was to compare canal transportation and centering ability of K 3 (0.02% taper) and K 3 (0.04% taper) with stainless steel hand K files in primary teeth using a spiral computed tomography (SCT) scan. Materials and Methods: A total of 75 extracted mandibular primary second molars was collected. Canals were divided randomly into three groups of 25 teeth each. Group I: K 3 files (0.02% taper), Group II: K 3 (0.04% taper), and Group III: Stainless steel hand K files. Three regions from apical, mid-root, and coronal levels of the canal were recorded. All the teeth were scanned before and after instrumentation by using SCT. Results: K 3 (0.02% taper) showed less canal transportation and a better centering ratio than K 3 (0.04% taper) and stainless steel hand K files. Statistical Analysis: The mean values were compared between different study groups and the P-value was calculated by using Kruskal-Wallis one-way ANOVA. The Mann-Whitney U-test followed by the Bonferroni correction method was employed to identify the significant groups at the 5% level. Conclusion: K 3 (0.02% taper) shaped root canals without significant shaping errors when compared to K 3 (0.04% taper) and stainless steel hand K files in primary teeth.